Inherent Environmental Protection Analysis For Process Plant - NURUL AIMIE BT MOHAMAD, NURUL AIMIE (Universiti Teknologi Petronas, 2009)
This paper presents an approach considering environmental factor in earlier stage of designing a plant design. The objective of this research is to develop a framework using inherent concept to take consideration the environment factor in earlier design stage. This approach is developed to improve the available methods in minimizing the waste, effluent and pollution that been discharge to the environment. This approach will be applied in flow sheeting stage. The framework applies the inherent concept and takes into account the environmental factor such as waste, effluent and pollution issues to be assess as the pollutants. The result for each pollutant will be benchmarked to the environment indices that are following the environmental law. This research has developed a demonstrative tool by using HYSYS simulation and Microsoft Excel as the platform. This project will be test on a refinery plant model to approve that the framework can be realized. The tool was developed to minimize the waste, effluent and pollution in a propose process by using inherent environmental protection methods. It is expected that by using this developed inherent waste minimization and environment will reduce the amount of waste, effluent and pollution that are released to the environment.